The Success of the Bishop-Koop Surgery in Newborns with Meconium Ileus and Congenital Intestinal Atresia When Compared to Divided Stomas - Asad Iqbal, Gauri Shankar Pandit, Muhammad Tayyab Azam, Safina Karim, Hafiz Mubashir Rasool, Nahida Burki, Ranjana Kumari Pandit, Nadeem Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to compare the Bishop-Koop procedure (BK) to the divided stoma in newborns with meconium ileus (MI) and congenital intestinal atresia. Study Design: Retrospective study Place and Duration: Children Hospital PIMS.Dec-2021-Jun 2022 Methods: There were seventy six neonates were presented in this study. Included neonates had meconium ileus (MI) and congenital intestinal atresia (CIA) and admitted to Hospital for surgery. Pateints were equally divided in two groups. Group I received divided stoma (DS) among 38 neonates and group II received Bishop-Koop procedure (BK) in 38 cases. Outcomes among both groups were compared in terms of surgery time, complications, and hospital stay. Mean standard deviation was used for data presentation. Results: There were 42 males (21 in each group) and 34 female (17 in each group) neonates among all cases. Mean age of the neonates in group I was 8.5 ± 4.16 days. Meconium ileus was found in 21(55.3%) in group I and 20 (52.6%) in group II and the rest of the neonates among both groups had congenital intestinal atresia. Mean operative time in group I was higher 180.7 ±9. 34 minutes as compared to group II 110.3 ± 7.26 minutes. We found that hospitalization in group II was lower 3.11 ±5. 40 days as compared to group I 10.2± 9.17 days. Frequency of complications in group I was higher found in 8 (21.5%) cases as compared to group II in 4 (10.5%) cases. Conclusion: In comparison to DS ostomies, we came to the conclusion that the BK approach is a safe, dependable, and acceptable technique for newborn surgery with a low risk of complications and shorter operating time and duration of hospital stay after ostomy closure. Keywords: Divided Stoma, Bishop-Koop, Meconium ileus , Congenital Intestinal Atresia, Complications